Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Berbantuan Media Poster Terhadap Hasil Belajar IPA Terpadu Di SMP Negeri 1 Waibakul - ., Natania Rambu Baba Niria; ., Yohana Makaborang; ., Anita Tamu Ina (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This research was conducted to determine the effect of using the Team Games Tournament (TGT) type of cooperative learning model on the science learning outcomes of class VIII students on the human circulation system material at SMP Negeri 1 Waibakul. The research method uses a quasi experiment, this study uses class VII-A as the control class and class VIII-C as the experimental class. The research design uses a nonequivalent control group design. This study used a sample of 72 students using non-probability sampling. Learning outcomes in the cognitive domain are obtained from pretest and posttest scores. Student learning outcomes were analyzed using statistical analysis and inferential statistics in the form of a t test. The results of the analysis obtained that the average value of the experimental class posttest was 85.33 and the control class posttest was 61.97. Based on testing the hypothesis with the t test at α = 0.05, a sig (2-tailed) value of 0.000 is obtained so that it can be concluded that H1 is accepted and H0 is rejected, meaning that there is an effect of using the Team Games Tournament (TGT) cooperative learning model on students' natural science learning outcomes. VIII on human circulatory system material at SMP Negeri 1 Waibakul.